Are smartphones and tablets influencing the quality of sleep? An Italian answer. - Fabrizio Bert; Maria Rosaria Gualano; Sebastian Giacomelli; Maria Martorana; Roberta Siliquini (Epidemiology, Biostatistics and Public Health)
Background: Electronic media use may affect sleep health. The present study aimed to estimate the association between technological devices usage, especially mobile phone, during the evening/night and self-reported sleep disorders.